2020
DOI: 10.3390/mti4020010
|View full text |Cite
|
Sign up to set email alerts
|

Improving Children’s E-Safety Skills through an Interactive Learning Environment: A Quasi-Experimental Study

Abstract: There is a worldwide concern for young children’s online safety and a growing necessity for e-safety skills to be taught to children from a young age as part of formal schooling. The purpose of this study was to design and evaluate the effectiveness and motivational capacity of an interactive web-based learning environment for improving children’s e-safety skills. A quasi-experimental pre-test post-test control group design was used with an experimental group of 48 sixth-grade primary school students, who used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Older students potentially have stronger views on events and venues represented in the digital tour, which are difficult to change as a result of a short interaction with the tool. In contrast, the literature supports that young children's attitudes can be positively affected even through relatively short term digital interventions at the primary education level [30], [31]. Therefore, there is support, both from the literature and from the present study's findings, for targeting young children in future, large-scale interventions attempting to resolve conflictual pasts and lead to social change through the use of virtual tours.…”
Section: Discussionsupporting
confidence: 41%
“…Older students potentially have stronger views on events and venues represented in the digital tour, which are difficult to change as a result of a short interaction with the tool. In contrast, the literature supports that young children's attitudes can be positively affected even through relatively short term digital interventions at the primary education level [30], [31]. Therefore, there is support, both from the literature and from the present study's findings, for targeting young children in future, large-scale interventions attempting to resolve conflictual pasts and lead to social change through the use of virtual tours.…”
Section: Discussionsupporting
confidence: 41%
“…The fact that a quasi-experimental design was used, in which the control group did not participate in an innovative intervention and did not receive any instruction, threatened the study's internal validity; a limitation commonly reported in quasi-experiments in the social sciences [43][44][45]. As previously mentioned, the data collected by control group participants might have been affected by factors such as "secondary" treatment infusion [39] and positive self-presentation [40].…”
Section: Limitationsmentioning
confidence: 99%
“…Previous research on preventing, addressing, and mitigating bullying in children's lives includes a wide range of technologies and apps, designed by adults: from online lessons to various platforms (Rubin-Vaughan et al, 2011;Timmons-Mitchell et al, 2016;Sánchez and Chamucero, 2017;Nicolaidou and Venizelou, 2020) chatbots (Young Oh et al, 2020), virtual storytelling apps (Hall et al, 2006(Hall et al, , 2009Enz et al, 2008;Watson et al, 2010;Vannini et al, 2011), and games (Raminhos et al, 2015;Calvo-Morata et al, 2019;Kolić-Vehovec et al, 2020;Paracha et al, 2020). Online learning applications are a popular mechanism to raise awareness, educate, and impart skills to children on how to manage their everyday experiences.…”
Section: Applications For Preventing and Addressing Bullyingmentioning
confidence: 99%